Influence of pH and Temperature on Enumeration of Cellulose- and Hemicellulose-Degrading Thermophilic Anaerobes in Neutral and Alkaline Icelandic Hot Springs - Mathrani, Indra M. (1993)
Cellulose- and hemicellulose-degrading thermophilic anaerobes were enumerated in biomat samples of various temperatures from two different hot springs in the Hveragerǒi area of Iceland: one spring had a pH near 7, the second had a pH near 9. The most-probable-number technique was used for enumeration of bacteria in the samples, with media at many different temperatures (37 to 90°C) and two pH values (7 and 9). There were generally more xylan-degrading then cellulose-utilizing organisms in both environments. There was no growth at 80°C in the neutral spring or at 37°C in the alkaline spring. However, there were large numbers of both types of organisms in the alkaline spring at 80°C and in the neutral spring at 37°C. No cultures grew from the most-probable-number tubes inoculated with the Hveragerǒi samples and incubated at 90°C or with media at pH 9. However, xylan-degrading cultures at 70°C were enriched at pH 9 with samples from some other Icelandic hot springs.